The Impact of Energy Investments on Employment: The Russian Case - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2023)
This study aims to analyze the causality relationship between total energy sector investments and employment for the years 1997-2021 in the framework of Russia using the Least Squares method. For this reason, panel analysis was used. First of all, necessary assumption tests were made for the establishment of the model. When the findings are evaluated, a significant relationship has been determined between energy and employment in Russia. In other words, there is a significant relationship between the type of investments made in the energy field and employment in Russia, which has an important patency in the world energy sector. That is, the 1 percent increase in investments in the energy field in this country means twice as much in explaining the employment rate. This is indeed an expected result for Russia, which has an important share in the world energy sector.